The effectiveness of problem-solving therapy augmented spirituality on positive emotions and mental health: A pilot study - Forooshani, Sayedhabibollah Ahmadi (Journal of spirituality in mental health, 2020)
This study aimed to investigate the effect of problem-solving therapy augmented spirituality on positive emotions and mental health in undergraduate students. The experimental group (n = 15) participated in ten sessions of the intervention, while the control group (n = 15) received no intervention. Oxford Happiness Questionnaire, Snaith-Hamilton Pleasure Scale, and General Health Questionnaire-28 were used for pretest, posttest and follow-up assessments. The results showed significant improvements in happiness, pleasure, and mental health at both posttest and follow-up assessments. In conclusion, the intervention can be considered as an effective intervention to improve positive emotions and mental health of university students.